[Fjord Off Akureyri, Iceland] - Streng, Evelyn Fiedler (1975)
Photograph of the fjord and mountains along Akureyri, Iceland. Grass covered, rounded mountains create a valley below grey and white clouds in the distance. The grey fjord sits in the foreground, white houses sparsely dotted along the coast of it in the background. Dark rocks sit in the bottom right corner of the photograph peeking out of the water.